The spiritual world of the individual and spiritual values - Chhaidze, A. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article describes the views of scientists on the inner world of the individual, certain basic human spiritual needs, and different views on moral values.
Keywords: spiritual; moral values